Poultry tariffs : levelling the playing field or rewarding inefficiency? (B) - Hobbs, Jacklynne; Draper, Peter, 1966- (London : Wits Business School, 2015)
In July 2013, Siyabulela Tsengiwe - chief commissioner of the International Trade Administration Commission of South Africa (ITAC) - and ITAC commissioners met to make a final determination on a highly contentious customs tariff application. The South African Poultry Association (SAPA) had asked for increased duties across a range of chicken products, claiming that cheap imports were threatening the survival of local and regional producers. The application was opposed by the Association of Meat Importers and Exporters (AMIE), on the grounds that it was intended to protect a sector with questionable ethics and an outdated business model. Tsengiwe and the commissioners had to decide which argument carried more weight in light of the government's wish to support agriculture in a frequently inequitable global trading environment, while ensuring that this support did not come at the expense of the poor.
Originally published in Hobbs, J., & Draper, P. (2015). Poultry tariffs: Levelling the playing field or rewarding inefficiency? (B). WBS-2015-4. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tsengiwe, Siyabulela; International Trade Administration Commission of South Africa; South African Poultry Association; Association of Meat Importers and Exports; Tariff on poultry